2019
DOI: 10.1016/j.jcis.2019.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-supramolecular gels: Adsorbents for chromium(VI) removal from wastewater

Abstract: Francesca (2019) 'Carbohydrate-supramolecular gels : adsorbents for chromium(VI) removal from wastewater.', Journal of colloid and interface science., 548 . pp. 184-196. Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 63 publications
2
30
1
Order By: Relevance
“…When weaker colloidal forces are active, and the gel exhibits the lowest stiffness (tan δ), the matrix is likely more able to accept PhAC molecules and reorganize around them. This also agrees well with the more pronounced self-healing ability of the above gel and is in line with some hydrogels’ adsorption capacities for metal ions [24].…”
Section: Resultssupporting
confidence: 89%
“…When weaker colloidal forces are active, and the gel exhibits the lowest stiffness (tan δ), the matrix is likely more able to accept PhAC molecules and reorganize around them. This also agrees well with the more pronounced self-healing ability of the above gel and is in line with some hydrogels’ adsorption capacities for metal ions [24].…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, with the exception of L‐Trp‐based eutectogel, higher efficiencies were detected in the presence of mechanically stronger gels, as accounted for by G’ values. The above result is different from the one we previously collected by using gels for dyes or Cr(VI) removal and sheds light on the effect of the solvent nature in determining materials performance . Furthermore, taking in consideration the side chain structure of the gelators, the above trend evidences a clear superior performance of the gels formed by amino acids with aromatic side chains over those with aliphatic ones, suggesting that adsorption of RhB, in this case, is mainly driven by π‐π stacking interactions.…”
Section: Resultscontrasting
confidence: 76%
“…Supramolecular gels have proven successful to remove a diverse range of dissolved pollutants or oil spills from water . In this context, we have recently shown that these materials allow fast and thorough removal of dyes from water with high recyclability, fuel desulfurization, as well as remediation of Cr(VI) polluted waters . Although the obtainment and use of ionic liquid gels has recently gathered a certain interest, the attention for eutectogels is less common .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solidified gasoline layer was then scooped out of the biphasic mixture and distillation was used to separate the gasoline from the gelator, so the gasoline could be recovered and the gelator could be recycled. Rizzo et al designed and synthesized imidazolium salt carbohydrate derivatives as supramolecular ionic liquid gelators ( Figure 74) [132]. The imidazolium cations contain long alkyl chains, making them the component that contributes to aromatic-aromatic interactions as well as the hydrophobic interactions.…”
Section: Applications Of Sugar-based Lmwgs 41 Environmental Remediamentioning
confidence: 99%